TOY肥料厂经典新编戏剧中的翻译策略 ：以《咏蟹花》中的诗为例 = Translation strategies of old tales retold in Toy Factory’s plays : a study on the translation of the poems in The Crab Flower Club - 江玮婷 Kang, Wei Ting (2019)
随着翻译研究的深入,许多学者开始将翻译与多种学科相结合来研究。然而, 有关戏剧翻译的学术研究却相当有限,其原因在于戏剧翻译需要考虑到原语及译语 以外的因素。这些因素就包括了史奈尔•霍恩比(Snell-Hornby)所言 “可演的可 说性”(Playable Speakability)中的可表演性与可念性这两个概念。为达到这两个 标准,孟伟根在〈戏剧翻译的方法〉中,介绍了六种戏剧翻译的方法与技巧,如加 词法、替代法、变通法、省略法、补偿法和释译法。TOY 肥料厂的第三本名为《似水阳刚》的剧本集中收录了关于女性题材的剧 目,如《东渡》、《妖精》、《咏蟹花》等。灵感来自《红楼梦》“蟹宴”情节的 《咏蟹花》,是 TOY 肥料厂艺术总监吴文德的第一部英语剧。 剧中,吴文德引用 并翻译了七首曹雪芹所写的诗。本文便是通过文本细读的方式结合上述理论,以 《咏蟹花》中的七首诗为文本,分析译者在翻译时所运用的原则与策略。整体来说, 译者采用的是安德烈•勒菲弗尔的理解翻译和散文翻译策略。若是以各别诗文分析, 则大多数使用直译与意译、加词法与省略法来翻译。As translation studies deepens, many researchers have conducted their research by combining translation studies and other studies. However, there is limited research in theatre translations. This is because theatre translation requires researchers to consider other components apart from original text and translated text. These components include “performability” and “speakability” in the concept of “playable speakability” mentioned by Snell-Hornby. In order to fulfill these components, Weigeng Meng introduced six different theatre translation skills required in his book titled “A Study of Drama Translation”. Those six skills are addition, substitution, alteration, abbreviation, compensation and explanation. In Toy Factory’s third book on plays about women, they included The Eastern Line on My Palm, Spirits and The Crab Flower Club. Originated from The Red Chamber’s crab feast plot, The Crab Flower Club was Toy Factory’s artistic director, Goh Book Teck’s first English theatre performance and he translated seven poems that were written by Cao Xueqin in the show. Using the method of close reading and the theories mentioned above, this research would analyze the translation of the seven poems as a whole and individual. As a whole, Goh used André Lefevere’s interpretation approach and prose translation method to translate. As an individual poem, most of the poems used literal translation, free translation, amplification and omission.